Feminized vaccine? Parents’ attitudes toward HPV vaccination of adolescents in Poland: A representative study - Tomasz Sobierajski; Ilona Małecka; Ewa Augustynowicz (Human Vaccines & Immunotherapeutics, 2023)
In 2023, the process of gradually introducing universal, free HPV vaccination into the vaccination program for children in Poland began. For this reason, the attitudes of parents of adolescents toward these vaccinations were examined in this study. The survey was conducted among 360 parents of children (girls and boys) aged 9–15. To achieve the best possible representativeness of the sample, parents were selected for the survey using a random-quota method. The survey was carried out using the CATI. The surveyed parents declared a high level of knowledge about HPV and awareness of HPV vaccination (74.2% of parents had heard of HPV, and 61.4% had heard of the HPV vaccine). The study showed a statistically significant relationship between parents’ education and knowledge of HPV infection – the higher the parent’s (mother or father) education, the higher the declared knowledge. Education was also a statistically significant factor influencing the declaration of vaccinating a child against HPV. In addition to parental education, the gender of the child was also a significant factor influencing willingness to vaccinate against HPV. Parents of boys were significantly more likely – than parents of girls – to declare that they would not vaccinate their sons against HPV. A significant factor influencing declarations to vaccinate against HPV was the child’s vaccination against COVID-19. The study results indicate a strong correlation between parental education and parental knowledge and attitudes about HPV and the HPV vaccine.